Population genetic data of 38 insertion-deletion markers in six populations of the northern fringe of the Iberian Peninsula. (March 2017) - Cardoso, Sergio; Sevillano, Rubén; Gamarra, David; Santurtún, Ana; Martínez-Jarreta, Begoña; de Pancorbo, Marian M.
Highlights: Comprehensive dataset of 38 INDELs in 575 samples from northern Iberian Peninsula. Forensic parameters are highly informative in the six populations analyzed. Population substructure and local inbreeding may affect forensic estimations. Abstract: Insertion-deletions have been reported very useful markers for forensic purposes. To further deepen in this matter, 38 non-coding bi-allelic autosomal indels were analyzed in 575 individuals representing six populations from the northern fringe of the Iberian Peninsula. Autochthonous populations from the Basque Country, northern Navarre, the Pas Valley in Cantabria and Aragon were analyzed, together with non-autochthonous populations from the Basque Country and northern Navarre. At the intra-population level, all loci analyzed were in Hardy-Weinberg equilibrium except for marker rs33917182 in autochthonous Basques. Linkage disequilibrium (LD) test did not reveal statistically significant allelic association between the different loci pairs in all six populations. Forensic parameters proved to be highly informative in the six populations analyzed, even if a scenario with population substructure and local inbreeding was considered for match probability calculations, and the potential of this indels set to be used in combination with other genetic markers is remarkable. As for inter-population analyses, in general terms the six populations showed low but statistically significant genetic distances. However, though this indels set efficiently differentiate between main ancestries, it does not allow an accurate separation at a local level and, for the time being, their combination with other informative markers is needed to maximize the power to accurately differentiate populations with close genetic ancestry.